Penyuluhan Manajemen Laktasi pada Ibu Postpartum Primipara di Puskesmas Bara – Baraya Kota Makassar - Haryati Sahrir; Rahayu Rahayu; Rahmaniar Rahmaniar; Nurmala Kamal (Pusat Riset dan Inovasi Nasional, 2022)
Lactation management is needed to support the successful management of breastfeeding. Failure of the breastfeeding process is often caused by some mothers who do not understand the correct way to breastfeed. Based on UNICEF data, only 30% of post partum primiparous mothers provide exclusive breast milk, this shows that babies in Indonesia still receive non-exclusive breast milk. The aim of this service is to increase knowledge about lactation management which consists of how to breastfeed, the benefits of breastfeeding, the correct breastfeeding position. The activity was carried out at the Bara Baraya Community Health Center, Makassar City on December 9 2022. The method used in this service was lecture and question and answer which began with a pre-test then providing information and then a post-test with a total of 7 participants. The results of the activity showed that those who had good knowledge before the counseling were carried out were 3 people (42.85%) and after the counseling it increased to 7 people (100%), this shows that the counseling was effective in lactation management for Primiparous Postpartum Mothers..